Occupational Safety, Health, and Awareness as Determinants of Productivity: A PLS-SEM Study of Construction Workers in Malang - Fifi Damayanti; Suhudi; Sigit Febrianto, Redi (Asian Journal Science and Engineering, 2025)
This study investigates the influence of Occupational Safety and Health (OSH) practices—comprising Occupational Safety, Occupational Health, and OSH Awareness—on worker productivity within construction projects in Malang, Indonesia. Using a quantitative approach with survey data from 63 construction workers and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that all three OSH components have a significant and positive impact on productivity. Occupational Health emerged as the strongest predictor (β = 0.377), followed by Occupational Safety (β = 0.350) and OSH Awareness (β = 0.312). Collectively, these variables explain 81% of the variance in worker productivity (R² = 0.810), underscoring the central role of OSH implementation in project performance. The study highlights that tangible investments in worker health and safety are not only ethical imperatives but also strategic drivers of efficiency. It concludes by recommending that construction managers treat OSH not as a regulatory formality, but as a critical asset for enhancing workforce output.